2013
DOI: 10.19026/rjaset.5.4447
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of Information Systems Factors on Trust in E-Government Initiative Adoption in Palestinian Public Sector

Abstract: The study conducted a primary investigation into the relationship between information system and trust in e-government followed by a secondary one into the relationship between trust in e-government and intention to use. It followed a quantitative approach of data collection through the use of questionnaire survey. The findings revealed that information quality, system quality, service quality, perceived usefulness, perceived ease of use, and securityprivacy contributed positively to trust in e-government whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 36 publications
(46 reference statements)
4
27
0
Order By: Relevance
“…Moreover, perceived information security (H5) was identified as a significant factor that is associated with the acceptance of social network sites in e-Learning (ß = 0.204, t = 5.161, p <0.05). A result is matched with the study of [78], who found that information security positively impacts www.ijacsa.thesai.org trust in E-government acceptance. Therefore, the students more perceived information security follows a tremendous student"s acceptance of social network sites in e-Learning, meaning high perceived information security attracts students to use the e-Learning system.…”
Section: B Model Analysissupporting
confidence: 74%
“…Moreover, perceived information security (H5) was identified as a significant factor that is associated with the acceptance of social network sites in e-Learning (ß = 0.204, t = 5.161, p <0.05). A result is matched with the study of [78], who found that information security positively impacts www.ijacsa.thesai.org trust in E-government acceptance. Therefore, the students more perceived information security follows a tremendous student"s acceptance of social network sites in e-Learning, meaning high perceived information security attracts students to use the e-Learning system.…”
Section: B Model Analysissupporting
confidence: 74%
“…On the other hand, Almahamid et al (2010) discovered that there exists a positive relationship between the intention to use e-government services and information quality. Similarly, Ayyash et al (2013) also stated that perceived information quality positively has a significant impact on the user's trust in the initiative of adopting e-government in public organizations. However, very few researches have studied the effect of information quality dimensions on the satisfaction of customers towards the Palestinian Ebanking services sector.…”
Section: Information Quality Dimensions and Customer Satisfaction Towmentioning
confidence: 98%
“…Privacy risk relates to the loss of control over personal information whereas, security is related with unauthorized access to individual's personal data is using government social media services. Ayyash, Ahmad and Singh [40] indicated the positive influence of both security and privacy in context of e-government services. Similarly, Ranaweera [25] also found a positive relationship between perceived security and perceived privacy on citizens trust in e-government services.…”
Section: Risk Factorsmentioning
confidence: 99%
“…The results of previous studies have found that if the e-government website provides accurate and timely information, users tend to use that technology for government services. According to Ayyash, et al [40], a good information quality information (timely, up to date, comprehensive, relevant) will develop citizens trust to use e-government services. There are variety of information on social networking services generated by multiple users.…”
Section: Social Media Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation